Fungsi Kata Bantu To dalam Cerita Pendek Itazuragitsune Karya Kubo Takashi - Hesti Marlena (Universitas Dian Nuswantoro, 2021)
This paper discusses the analysis of particle “to” function in the short story entitled Itazuragitsune by Takashi Kubo. The purposes of this thesis are to determine the function of particle “to” and to determine the structures and elements of the sentences in the book. The writer used the qualitative descriptive analysis method. It focusses on the reasons and the ability of the writer to express the study of language based on the data. The results show that there are ten functions of particle “to”. Among the ten functions of particle “to”, there are three functions of particle “to” that have the most categories based on the similarity of function of particle “to”. They served as a link between two different clauses, as a particle of quotations, and as an imitation of adverb of an onomatopoeic.